FENOMENA PERUBAHAN BENTUK MOBIL TOYOTA KIJANG GENERASI I (1977), GENERASI II (1981) DAN GENERASI III (1986) SEBAGAI REPRESENTASI DARI KEINGINAN, KEBUTUHAN, DAN DAYA BELI MASYARAKAT PENGGUNANYA DI INDONESIA - Ahmad Nurzaeni Fauzi (ARTic, 2019)
This research is study of a design object that can change based on time, the purpose is to examine what aspects are encourage the design changes of Toyota Kijang 1st generation (1977-1981), Toyota Kijang 2nd generation (1981-1986) And Toyota Kijang 3rd generation (1986-1992). The analytical method that used in this thesis is the Principle of Totality, Principle of Time, and Principle of Value by W. H. Mayall and developed by Dr. Ahadiyat Joedawinata to analyze the features that contained in Toyota Kijang's exterior and exterior components, and examine what factors are missing, what's changed, what's fixed, and what's new from the 3 generation Toyota Kijang. The results of this study concluded that the design aspect of a function (performance) and aesthetic (form) are related to each other, a change in one aspect affects the other aspects. As for the changes that occur in a design influenced by aspects of non-design. In this case of a shift form of the Toyota Kijang cars changes motivated by 3 (three) factors include: Human Factors (need, will and capability), Economical Factors and Technological Factors.